Protests by journalists in competitive authoritarian regimes: repertoire and impact in the case of Ukraine (2010-14). Issue 1 (2nd January 2023) - Pleines, Heiko; Somfalvy, Esther
ABSTRACT: Studies of competitive authoritarian regimes regularly emphasize the political importance of media ownership, commonly assuming that the owners' views are mirrored in the journalists' writing and thus depriving journalists of a distinctive role. We move beyond this narrow perspective, analysing anti-regime protests by journalists in order to develop a better understanding of their role in competitive authoritarian regimes. Our exploratory case study of Ukraine—comparing the stable regime (2010-13) with the Euromaidan protests in late 2013/early 2014— is based on a protest event database of media freedom-related protest actions by journalists (N = 209) and interviews with journalists (N = 31). We examine protest forms, coalition building, claims and targets. To understand journalists' agency in relation to political regime dynamics, we also look at their long-term engagement in contentious politics. While our results show that journalists' own protest actions are not game changers, mainly due to journalists' unwillingness to forge larger coalitions, the politicization of journalists, which leads to political activism and, most importantly, the creation of new media outlets with a political agenda, is an important element in regime dynamics and regime change.